2016
DOI: 10.3109/02688697.2016.1173192
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystalline hydroxyapatite intervertebral cages induce fusion after anterior cervical discectomy and may be a safe alternative to PEEK or carbon fiber intervertebral cages

Abstract: This series provides evidence that nHA intervertebral cages can successfully promote fusion after ACDF and may provide an alternative to carbon fiber and PEEK cages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
1
1
0
1
Order By: Relevance
“…These results to some extent were in accordance with those of recent and related reports, as it had been shown that HA/PA composite has a positive effect on osteoblast adhesion, viability, and differentiation, thus influencing the bone cell responses as it comes in contact with HA/PA substrate [3639]. …”
Section: Discussionsupporting
confidence: 92%
“…These results to some extent were in accordance with those of recent and related reports, as it had been shown that HA/PA composite has a positive effect on osteoblast adhesion, viability, and differentiation, thus influencing the bone cell responses as it comes in contact with HA/PA substrate [3639]. …”
Section: Discussionsupporting
confidence: 92%
“…Case series, described by Timothy et al, have demonstrated 100% bony fusion promotion after using HApN cages in ACDF without serious side effects. Moreover, HApN cages have shown a higher tolerance to torsion, shear, and compression forces when compared to other synthetic cages such as a PEEK [109].…”
Section: Nanohydroxyapatite Cagesmentioning
confidence: 99%
“…Кейджі з нанокристалічного ГA (Nanoss ® -Cervical, Pioneer ® Surgical Technology, Inc., Marquette, MI), у якого розміри кристалів подібні до природної кістки, показали ефективність при проведенні передньої цервікальної дискектомії та спондилодезу (ACDF) [42].…”
Section: клінічні спостереженняunclassified